Kajian produksi dan produktivitas nelayan pancing tonda di Desa Malalanda Kecamatan Kulisusu Kabupaten Buton Utara - Aksar, Al; La Ola, La Onu; Rosmawati; Annaastasia, Nurhuda; Risfandi (Universitas Halu Oleo, 2024)
The purpose of this study was to examine the volume of production of trolling line fishermen who caught fish in wakatobi waters and in kamaru waters, as well as to examine the productivity of trolling line fishermen who caught fish in wakatobi and kamaru waters. This research was conducted in the village of malalanda, kulisusu district, north buton regency, during the period from july to august 2020. The population in this study was determined using the census method. The number of samples in this study were 21 people. The analysis used is descriptive quantitative analysis using the method of production analysis and productivity analysis. Based on the results of the analysis and discussion obtained, it shows that the production of trawling fishing rods in the village of malalanda who catches in the kamaru waters area, the highest is 210 kg/month, the lowest is 150 kg/month, and the production of fishing rods in the village of malalanda is catching fish in wakatobi waters, the highest is 345 kg/month, the lowest is 225 kg/month. The productivity of fishing rods in the village of malalanda who make fishing in the kamaru waters area, the highest productivity is Rp. 1,75/month, the lowest is Rp. 1,55/month, and the productivity of trolling fishermen in the village of malalanda who do fishing in the wakatobi waters, the highest productivity is Rp. 2,22/month, the lowest is Rp. 1,855/month.